INTERFERENSI BAHASA DALAM FILM KELUAR MAIN 1994 KARYA ELVIN MIRADI DAN MOHAMMAD SABEG - Waode Dewi Handayani; Rizky Fitriyanti Pradani; Siti Rohmatul Ummah; Devito Andharu; Sri Utami; Suhartawan Budianto (Universitas Pendidikan Ganesha, 2026)
Penelitian berjudul